2011
DOI: 10.4103/0976-237x.86466
|View full text |Cite
|
Sign up to set email alerts
|

Compound odontoma associated with an unerupted rotated and dilacerated maxillary central incisor

Abstract: Odontomas are benign tumors containing various component tissues of teeth. They usually remain asymptomatic and are diagnosed on routine radiographs. Clinically, they are often associated with delayed eruption or impaction of permanent teeth and retained primary teeth. A case of compound odontoma in association with an unerupted, rotated and dilacerated maxillary permanent right central incisor in a 12-year-old boy is reported. Such combination is rare, making it an interesting case for reporting. We have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 6 publications
1
10
0
7
Order By: Relevance
“…The most common location was the anterior region of maxilla2,12,15 and the incisor lesion was diagnosed and treated earlier than the canine or third molar lesions 14. In the present study, the most common locations were, respectively, the canine region for the compound odontoma and the molar region for the complex odontoma, which corresponded with the reports of Kulkarni et al7 and da Costa et al16 Odontomas rarely involved the primary dentition (1.3-12.8%)2,15 and in the current study, none of the odontoma involved the primary dentition.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most common location was the anterior region of maxilla2,12,15 and the incisor lesion was diagnosed and treated earlier than the canine or third molar lesions 14. In the present study, the most common locations were, respectively, the canine region for the compound odontoma and the molar region for the complex odontoma, which corresponded with the reports of Kulkarni et al7 and da Costa et al16 Odontomas rarely involved the primary dentition (1.3-12.8%)2,15 and in the current study, none of the odontoma involved the primary dentition.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have reported various disturbances to tooth eruption related to odontomas 2,5-7,9,14,16,18,19. Katz14 studied 396 cases of odontomas in all age groups and found that 41% were associated with unerupted teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foram descritos pela primeira vez por Paul Brocain em 1867 3 , e geralmente apresentam-se como uma massa anormal de tecido dentário calcificado, representando uma anormalidade com variáveis de tamanho e forma 1 . Dos tumores odontogênicos, é o que se apresenta com maior frequência nos maxilares e geralmente são encontrados em exame radiográfico de rotina, sendo caracterizado por seu crescimento lento, comportamento não agressivo e são diagnosticados entre a segunda e terceira décadas de vida 4,5 .…”
Section: Introductionunclassified